QUANTIFICATION OF ANGIOGENESIS IN THE CHICKEN CHORIOALLANTOIC MEMBRANE (CAM) - Blacher, Silvia; Devy, Laetitia; Hlushchuk, Ruslan; Larger, Etienne; Lamandé, Noel; Burri, Peter; Corvol, Pierre; Djonov, Valentin; Foidart, Jean-Michel; Noël, Agnes (Image Analysis and Stereology, 2011)
The chick chorioallantoic membrane (CAM) provides a suitable in vivo model to study angiogenesis and evaluate several pro- and anti-angiogenic factors and compounds. In the present work, new developments in image analysis are used to quantify CAM angiogenic response from optical microscopic observations, covering all vascular components, from the large supplying and feeding vessels down to the capillary plexus. To validate our methodology angiogenesis is quantified during two phases of CAM development (day 7 and 13) and after treatment with an antiangiogenic modulator of the angiogenesis. Our morphometric analysis emphasizes that an accurate quantification of the CAM vasculature needs to be performed at various scales.